A Hydrophilic Supported Fe3O4 Catalyst with Enhanced Light Olefins Selectivity in the Fischer‐Tropsch Synthesis. Issue 34 (13th September 2021) - Ma, Long; Zhang, Yuxi; Gao, Xinhua; Atchimarungsri, Thachapan; Ma, Qingxiang; Zhang, Jianli; Zhang, Xingjun; Li, Caihu; Zhao, Tian‐Sheng
Abstract: A series of Fe3 O4 catalysts supported on chitosan (CTS) were prepared through successive hydrothermal synthesis, cross‐linking, and mechanical mixing of CTS. The prepared catalysts were characterized by SEM, XRD, N2 adsorption‐desorption, XPS, FT−IR, TG, H2 −TPR, CO−TPD, C3 H6 −TPD, and contact angle (CA) analysis, then evaluated for their performance in the Fischer‐Tropsch synthesis (FTS). CTS supported Fe3 O4 catalyst increased the hydrophilicity of the pristine un‐supported Fe3 O4 . Results revealed that the catalysts exhibit high activity with tuned product distribution in FTS. The water gas shift reaction is facilitated over the Fe3 O4 /CTS catalysts, and their selectivity for light olefins is significantly improved by inhibiting the secondary reaction of the initial olefins, which was confirmed by C3 H6 −TPD experiments. The Fe3 O4 particle size has a significant influence on product distribution, with larger Fe3 O4 particles being beneficial to the formation of light olefins. The 30 % Fe3 O4 /CTS catalyst has light olefin selectivity of 35 % with an O/P value of 2.19, which are higher than those of 21 % and 0.62 over the pristine Fe3 O4 . Abstract : Fischer‐Tropsch synthesis (FTS) is an alternative for synthesizing liquid fuels via CO hydrogenation. The Fe3 O4 catalysts supported on hydrophilic chitosan can tune the product distribution in FTS. The overall hydrophilicity of the catalyst surface inhibits the secondary reactions of olefins, thus obviously promotes the olefins selectivity in products.